Sense of Coherence Among Apprentices in Vocational Education and Training in Norway: Exploring General Resistance Resources in Work-Based Learning - Grete Hanssen; Britt Karin Utvær (European Research Network Vocational Education and Training (VETNET), 2022)
Purpose: A work life in the face of constant and rapid development requires highly qualified and motivated professionals who can deal with the stress and demands of the future. Through school- and work-based learning, upper secondary vocational education and training (VET) qualifies adolescents for professional practice. Aron Antonovsky introduced two fundamental concepts explaining how humans cope with stressful situations: The sense of coherence (SOC), which includes the concepts of comprehensibility, manageability and meaningfulness, and general resistance resources (GRRs), which are resources in the persons themselves (internal) and/or in their surroundings (external). This study aimed to identify and explore which GRRs contribute to SOC among apprentices in VET and how they influence work-based learning. Methods: Data were obtained from 10 VET students in Norway and generated at three timepoints: interviews during the final semester of school-based learning (spring 2020), interviews during work-based learning (spring 2022) and register data following trade certificate completion (summer 2022). The students' experiences of work-based learning as apprentices formed the basis of this study's analysis. The stepwise deductive-inductive method introduced by Tjora was used to generate and analyse the data. Findings: The apprentices' GRRs included emotional, professional, social, relational, material and cultural dimensions. GRR identification and utilisation were both individually and socially conditioned. Apprentices were able to identify, both consciously and unconsciously, internal GRRs to further identify external GRRs and vice versa. Each identified GRR in this study appeared to affect one, two or all three SOC components. Conclusion: A salutogenic VET can provide personal, social, environmental and physical resources (GRRs) that ensure coherent learning experiences. The roles and functions of teachers and supervisors in schools and companies are essential. By supporting VET students' SOC and helping them identify GRRs, they promote learning and healthy development as well as prepare highly qualified and motivated professionals.